Correlations Between Positive or Negative Utterances and Basic Acoustic Features of Voice: a Preliminary Analysis - Stolarski , Łukasz (Research in Language, 2022)
The major aim of this paper is to establish possible correlations between continuous sentiment scores and four basic acoustic characteristics of voice. In order to achieve this objective, the text of “A Christmas Carol” by Charles Dickens was tokenized at the sentence level. Next, each of the resulting text units was assessed in terms of sentiment polarity and aligned with the corresponding fragment in an audiobook. The results indicate weak but statistically significant correlations between sentiment scores and three acoustic features: the mean F0, the standard deviation of F0 and the mean intensity. These findings may be useful in selecting optimal acoustic features for model training in multimodal sentiment analysis. Also, they are essential from a linguistic point of view and could be applied in studies on such language phenomena as irony.